KEEFEKTIFAN PEMBELAJARAN MENULIS DENGAN PENDEKATAN WHOLE LANGUAGE DI SEKOLAH DASAR - Rukayah Rukayah; Suharno Suharno; Yenny I.S. Purwanti (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: The developmental study was intended to find out the test result of the effectiveness of writing teaching and learning by using Whole Language approach; and to obtain the appropriateness of the writing teaching and learning model by using Whole Language approach at Elementary schools. The steps of the study included preliminary study, model development, model try out, and dissemination. The results of the study suggested that (1) the writing competence of the students who learnt writing by using Whole Language approach was better than those who learnt writing conventionally; and (1) writing teaching and learning model by using Whole Language approach could be accepted by the stakeholders well.Keywords: writing skills, Whole Language approach, elementary schools.Abstrak: penelitian pengembangan ini bertujuan untuk menemukan hasil uji efektivan model pembelajaran menulis dengan pendekatan Whole Language di sekolah dasar; dan mendapatkan keberterimaan model pembelajaran menulis dengan pendekatan Whole Language di sekolah dasar. Langkah-langkah penelitian meliputi studi pendahuluan, pengembangan model, pengujian model, dan deseminasi. Hasil penelitian menunjukkan (1) kemampuan menulis siwa yang belajar menulis dengan pendekatan whole language lebih baik daripada kemampuan menulis siswa yang belajar menulis dengan cara konvensional; dan (2) model pembelajaran menulis dengan pendekatan whole language dapat diterima stakeholders dengan baik. Kata kunci: keterampilan menulis, pendekatan Whole Language, SD